Vulneración de los derechos de las personas con discapacidad en la aplicación de la normativa laboral - Bernal Gómez, Melany Nicole (2024)
Our country over the last few years has sought to promote through public policies respect for the rights of special groups, which have been victims of social exclusion for several periods, due to their different capacities or cognitive or physical deficiencies. The legal problem lies in the deficiency of the Ecuadorian legal system which currently has legislation on labor law that seeks to provide free access to the right to work, enshrined in the Constitution of the Republic of Ecuador and human rights instruments. However, we find a contrary position when this same right is limited by regulations that establish types of hiring where for every twenty-five stable workers companies must have a person with a disability, thus establishing a gap between the supposed inclusion that we are promulgating today and the reality that is visualized in companies..........